(untitled) (Research, Society and Development, 2022)
Background: Until now, technological advances and new surgical methods have been insufficient to reduce the elevated risk of mortality and morbidity in patients undergoing cardiac surgery. It is known that preoperative malnutrition is correlated with morbidity, mortality, hospital admission and quality of life after surgery. The prognostic nutritional index (PNI) is calculated from serum albumin levels and peripheral lymphocyte counts. Studies have shown that a low PNI is an independent short-term and long-term adverse prognostic factor. Objective: To assess whether the nutritional prognostic index is a good prognostic marker to predict complications and death in cardiac surgical patients. Methodology: A systematic review was carried out in PubMed, Lilacs and SciELO databases, with the following descriptors: prognostic nutritional index and cardiac and surgery. Articles that evaluated the PNI and complications, including death, in cardiac surgical patients were chosen. Results: Nineteen publications were analyzed and included in the systematic review, of which 13 were prospective observational studies and 6 were retrospective observational studies. Of these studies, 9 were comparisons with other indices, 4 on PNI and postoperative complications and 6 on PNI and mortality, most of the studies demonstrate that the PNI is a useful tool to point out mortality and postoperative complications. Conclusion: The results suggest that the PNI is a useful tool to point out the risk of death and complications in the postoperative period of cardiac surgeries, but a common cut-off point for surgery has not yet been established.